114 Impact of left ventricular ejection fraction on procedural and long-term outcomes of bifurcation percutaneous coronary intervention. (8th December 2021) - Gallone, Guglielmo; Bruno, Francesc; Filippo, Ovidio De; Cerrato, Enrico; Muscoli, Saverio; Trabattoni, Daniela; Mario, Carlo Di; Doronzo, Mattia; Conrotto, Federico; Escaned, Javier; Koo, Bon-kwon; D'Ascenzo, Fabrizio; et al.
Abstract: Aims: Longitudinal systolic function may integrate information on aortic stenosis (AS) natural history and cardiac comorbidities with potential prognostic implications. We explored the impact of tissue Doppler imaging (TDI)-derived longitudinal systolic function defined by the peak systolic average of lateral and septal mitral annular velocities (average S') among symptomatic patients with severe AS undergoing transcatheter aortic valve implantation (TAVI). Methods and results: 297 unselected patients with severe AS undergoing TAVI from January 2017 to December 2018 at three European centres, with available average S′ at preprocedural echocardiography were retrospectively included. The primary endpoint was the Kaplan Meier estimate of all-cause mortality. After a median 18 months (IQR 12–18) follow-up, 36 (12.1%) patients died. Average S′ was associated with all-cause mortality (per 1 cm/s decrease: HR: 1.29, 95% CI: 1.03–1.60, P  = 0.025), with a best cut-off of 6.5 cm/s. Patients with average S′ <6.5 cm/s (55.2% of the study population) presented characteristics of more advanced left ventricular remodelling and functional impairment along with higher burden of cardiac comorbidities, and experienced higher all-cause mortality (17.6% vs. 7.5%, P  = 0.007) also when adjusted for in-study outcome predictors (adj-HR: 3.33, 95% CI: 1.25–8.90, P  = 0.016). Results were consistent among patients with preserved ejection fraction, normal-flow AS, high-gradient AS and in those without left ventricular hypertrophy. Conclusions: Longitudinal systolic function assessed by average S' is independently associated with long-term all-cause mortality among unselected patients with symptomatic severe AS undergoing TAVI. In this population, an average S′ below 6.5 cm/s best defines clinically meaningful reduced longitudinal systolic function and may aid clinical risk stratification.